Scalp Nerve Block in Combination to General Anesthesia Lower the Increase of Inflammatory Markers Compared to General Anesthesia alone in Craniotomy Surgeries - Tjokorda Gde Agung Senapathi (Journal of Global Pharma Technology, 2020)
Background: Regional anesthesia reduces the inflammatory response and surgery-related immunosuppressive response. The scalp nerve block technique is a relatively simple and safe technique. The goal of this study was to compare the inflammatory response between a combination of general anesthesia and scalp nerve block compared with general anesthesia in craniotomy surgery. Methods: This was a double-blind, randomized controlled trial with pre and post-test study in 50 subjects carried out at Sanglah General Hospital (Bali, Indonesia). Group A treated with scalp nerve block using 0.25% levobupivacaine solution, and group B treated with scalp nerve block using 0.9% NaCl solution. Blood tests were carried out before and after the surgery to measure platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), and C-reactive protein (CRP) as inflammatory markers. Results: The mean difference of PLR, NLR, and CRP between the two groups were significantly different (p <0.001) at 72 hours after the surgery. The tests found no significant difference at before and right after the surgery (p >0.05). Conclusion: The application of scalp nerve block in combination to general anesthesia lower the increase of PLR, NLR, and CRP compared to general anesthesia alone in craniotomy surgeries.Keywords: PLR, NLR, CRP, Inflammation, Regional anesthesia.